2004
DOI: 10.1021/ie040220b
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Phase Oxidation of Benzene to Phenol over V-Substituted Heteropolyacid Catalysts

Abstract: The liquid-phase oxidation of benzene was carried out in aqueous acetic acid solvent over V-substituted heteropolyacids (V−HPAs) using molecular O2 and ascorbic acid as the oxidant and reducing reagent, respectively. Phenol was exclusively obtained as the oxygenation product. The elimination of the V species from the V−HPA (Keggin structure) catalyst into the reaction solvent during the benzene oxidation reaction was largely inhibited by ion-exchanging the proton of the V−HPA catalyst with Cs+. The main active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 13 publications
2
58
0
2
Order By: Relevance
“…Compounds of vanadium, due to their reactivity and remarkable stability, have been utilized as efficient catalysts for a variety of catalytic reactions [12][13][14][15][16], especially for the catalytic selective oxidation of benzene to phenol [17][18][19][20][21]. Recently, various vanadium containing mesoporous molecular sieves such as V-MCM-41 [22,23], V-MCM-48 [24] and V-SBA-15 [25,26] have been prepared by hydrothermal methods through different synthesis routes.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds of vanadium, due to their reactivity and remarkable stability, have been utilized as efficient catalysts for a variety of catalytic reactions [12][13][14][15][16], especially for the catalytic selective oxidation of benzene to phenol [17][18][19][20][21]. Recently, various vanadium containing mesoporous molecular sieves such as V-MCM-41 [22,23], V-MCM-48 [24] and V-SBA-15 [25,26] have been prepared by hydrothermal methods through different synthesis routes.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that H 2 O 2 can be stably present in the acidic medium as its selfdecomposition is inhibited [22,23]. Thus, the aqueous acetic acid solvent was chosen in this work.…”
Section: Catalytic Testmentioning
confidence: 99%
“…Yamaguchi et al reported the oxidation of benzene over the cesium salts of heteropoly acids (CsPMoV n , n=1-3) using O 2 as oxidant. [28] Compared with the application of cesium salts of heteropoly acids as catalyst in acid reactions and gaseous phase oxidation reactions, their application in liquid phase oxidation reaction as water-tolerant catalysts was rare. [29][30][31] From the synthetic point of view, the typical procedure for preparation of cesium salts of HPAs are generally proceeded through a solution method by titrating the controlled amount of an aqueous solution of Cs 2 CO 3 into the aqueous solution of HPA.…”
Section: Introductionmentioning
confidence: 99%